One step hydrothermal synthesis of magnetically separable rGO supported Fe₃O₄ and Ag nanoparticles for adsorption and reduction of organic pollutants - Eman F. Aboelfetoh (Scientific Reports)
Abstract The development of efficient adsorbents and catalysts is crucial for enhanced pollutant removal and catalytic performance. In this study, a magnetically separable rGO/Fe3O4/Ag nanocomposite was synthesized via a facile one step hydrothermal method, enabling simultaneous reduction of graphene oxide (GO) and in situ deposition of Fe3O4 and Ag nanoparticles. The nanocomposite’s structure, surface features, and magnetic properties were confirmed through appropriate characterization techniques. The nanocomposite exhibited high adsorption efficiency toward methyl violet 2B (MV), with performance evaluated across varying dye concentrations, pH, temperature, and adsorbent dosages. Statistical error analysis (reduced χ2, RMSE, SSE) validated the applicability of a pseudo-second-order kinetics. The adsorption data also fit Langmuir isotherm, revealing a maximum uptake (qmax) of 168.70 mg/g. Employing NaBH4 as reductant, the nanocomposite achieved rapid p-nitroaniline (p-NA) hydrogenation to p-phenylenediamine (p-PDA), achieving 97.60% conversion within 3 min and a rate constant of 0.95 min⁻1, consistent with pseudo-first-order kinetics. The nanocomposite’s strong magnetic responsiveness (Ms = 30 emu/g) enabled efficient separation and reusability, maintaining stable performance over five adsorption and eight catalytic cycles.